The Application of Discussion Method to Improve the Learning Outcomes of PAI Class V Students at Muhammadiyah Bangun Raya Elementary School - Ernida Lubis (BiCED Proceeding, 2024)
This study aims to improve student learning outcomes through the implementation of the Make a Match method in Islamic Religious Education at SD Muhammadiyah Bangun Raya. This research uses a classroom action research approach conducted in two cycles. The results show that in Cycle I, only 50% of students achieved the Minimum Completion Criteria (KKM), while in Cycle II, the percentage of students reaching KKM increased to 75%. This indicates that the Make a Match method enhances student engagement and learning outcomes. The study concludes that the implementation of this method is effective in improving the quality of learning in elementary schools.